1987
DOI: 10.1093/ageing/16.6.405
|View full text |Cite
|
Sign up to set email alerts
|

Narcolepsy in the Elderly: A Forgotten Diagnosis

Abstract: Two cases of narcolepsy presenting in elderly patients are reported. Delay in diagnosis prior to presentation resulted in considerable psychosocial problems for both patients. Satisfactory responses to therapy were achieved with patients regaining independence. Difficulties associated with this diagnosis in the elderly are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The few previously reported cases of NC with an onset at an older age were initially misdiagnosed and, thus, the diagnosis was delayed. In 1987, Kelly et al [5] reported 2 cases: the first was a male with symptom onset at 72 years and the second a female at 84 years. In both cases, the diagnosis of NC was considerably delayed (15 years in the first case, misdiagnosed as secondary epilepsy).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The few previously reported cases of NC with an onset at an older age were initially misdiagnosed and, thus, the diagnosis was delayed. In 1987, Kelly et al [5] reported 2 cases: the first was a male with symptom onset at 72 years and the second a female at 84 years. In both cases, the diagnosis of NC was considerably delayed (15 years in the first case, misdiagnosed as secondary epilepsy).…”
Section: Discussionmentioning
confidence: 99%
“…Possible later onset is indicated as rare throughout studies; in Roth [3], only 4 out of 288 cases had onset after 50 years. To our knowledge, only 3 cases of NC onset at around age 70 years have been described: all of them are not clinically clear [4, 5]. We would like to present an undoubtedly diagnosed late-onset NT1 in a 69-year-old male subject.…”
Section: Introductionmentioning
confidence: 98%
“…16 In others, mild disease severity, misdiagnosis or long delays in cataplexy expression may prevent proper diagnosis and treatment. 17,18 Chakravete and Rye 18 estimated that it first comes to medical attention after the age of 40 years in nearly half of affected patients. Rye and associates 19 stressed that, during differential diagnosis, narcolepsy should always be considered by physicians faced with an older patient experiencing sleepiness or with transient loss of muscle tone.…”
Section: Narcolepsymentioning
confidence: 99%
“…Even after finding mild obstructive sleep apnea and treating it with CPAP in our patient, her narcolepsy symptoms did not improve. The prevalence of narcolepsy in the elderly population is exceedingly rare but has been reported in a few cases [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…An article published in 1987 describes two cases of delayed diagnosis of narcolepsy in elderly patients causing significant psychosocial problems [ 13 ]. Another case report describes a 60-year-old patient who presented with classic narcolepsy with frequent cataplexy.…”
Section: Discussionmentioning
confidence: 99%